A flexible forcing immersed boundary-simplified lattice Boltzmann method for two and three-dimensional fluid-solid interaction problems. (30th April 2019) - Dash, S.M.
Highlights: Flexible forcing immersed boundary-simplified lattice Boltzmann solver is proposed. This solver needs less computational memory compare to conventional IB-LBM solvers. Applicability of the solver is shown for two and three-dimensional flow problems. Complex matrix calculation is avoided to accurately satisfy the no-slip condition. Abstract: In this paper, a novel flexible forcing immersed boundary-simplified lattice Boltzmann method (FFIB-SLBM) is introduced to efficiently simulate two and three-dimensional fluid-solid interaction problems. Here, the simplified lattice Boltzmann method (Chen et al. [1]) with benefits such as lower virtual memories, ease in the implementation of the physical boundary conditions and higher numerical stability over the standard lattice Boltzmann method is coupled with an implicit flexible forcing immersed boundary scheme (Dash et al. [2]) which accurately satisfies the no-slip condition for the unsteady and moving boundary problems. The proposed FFIB-SLBM solver not only avoids the complex mathematics involved in the large banded matrix inversion but also requires lesser computational memory resources compares to the conventional immersed boundary-lattice Boltzmann method. The capabilities and accuracy of the coupled FFIB-SLBM solver are checked with several two and three-dimensional fluid-solid interaction problems. The obtained results from FFIB-SLBM solver are noticed to be in very good agreement with the published literature.